Synthesis of Cu-ZnO and C-ZnO nanoneedle arrays on zinc foil by low temperature oxidation route: effect of buffer layers on growth, optical and field emission properties - Jamali-Sheini, Farid; Patil, K. R.; Joag, Dilip S.; More, Mahendra A. (Applied Surface Science, 2011)
Different densities of ZnO nanoneedle films have been prepared by pre-coated zinc foils with thin layer of copper and carbon followed by thermal oxidation at 400 degrees C in air. The X-ray diffraction patterns show well defined peaks, which could be indexed to the wurtzite hexagonal phase of ZnO. The scanning electron microscope images clearly reveal formation of ZnO needles on the entire substrate surface. The X-ray photoelectron spectroscopy studies indicate that Cu and C ions are incorporated into the ZnO lattice. Photoluminescence studies evaluate different emission bands originated from different defect mechanism. From the field emission studies, the threshold field, required to draw emission current density of similar to 100 mu A/cm(2), is observed to be 2.25 V/mu m and 1.57 V/mu m for annealed zinc foil pre-coated with copper and carbon, respectively. The annealed film with copper layer exhibits good emission current stability at the pre-set value of similar to 100 mu A over a duration of 4 h. The results show that buffer layer is an important factor to control the growth rate, resulting in different density of ZnO needles, which leads to field emission properties. This method may have potential in fabrication of electron sources for high current density applications. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Buffer layer; Carbon; Copper; field emission; Nanoneedle; ZnO

Surface characterization of Au-ZnO nanowire films - Jamali-Sheini, Farid; Yousefi, Ramin; Patil, K. R. (Ceramics International, 2012)
Au-ZnO nanowire films have been synthesized by annealing Zn foils coated with a thin layer of gold. An X-ray diffraction study found that the synthesized ZnO consists mainly of a hexagonal wurtzite structure along with a small amount of AuZn3 phase. Scanning electron images showed that the ZnO wires extend to several microns in length. X-ray photoelectron spectroscopy studies confirmed the oxidation states of Au and Zn. An asymmetric O ls peak indicates the presence of oxygen in an oxide layer and O H groups on the films surfaces. Photoluminescence (PL) spectra showed different visible peaks for pre-annealed films, while for annealed films an UV peak appeared. In addition, the PL analysis showed that the overall intensity of photoluminescence decreased significantly after the films were annealed. Raman spectroscopy results also indicated that the crystalline quality of the films improved with annealing. This could be attributed to a decrease in oxygen vacancies and/or absorption of O-H groups on the surface of ZnO film. The highly hydrophilic surface with a water contact angle of similar to 155 degrees was obtained after annealing in air. (c) 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Au-ZnO; Highly hydrophilic; Nanowires; XPS